Inflammatory Breast Cancer: The Cytokinome of Post-Mastectomy Wound Fluid Augments Proliferation, Invasion, and Stem Cell Markers - Alshaimaa Tarek; Shrouk Khalaf El-Sayed; Wendy A. Woodward; Mohamed El-Shinawi; Jon Mark Hirshon; Mona Mostafa Mohamed (Current Issues in Molecular Biology, 2022)
Inflammatory breast cancer (IBC) is an aggressive phenotype with a high recurrence and low survival rate. Approximately 90% of local breast cancer recurrences occur adjacent to the same quadrant as the initial cancer, implying that tumor recurrence may be caused by residual cancer cells and/or quiescent cancer stem cells (CSCs) in the tumor. We hypothesized that wound fluid (WF) collected after modified radical mastectomy (MRM) may activate cancer cells and CSCs, promoting epithelial mesenchymal transition (EMT) and invasion. Therefore, we characterized the cytokinome of WF drained from post-MRM cavities of non-IBC and IBC patients. The WF of IBC patients showed a significantly higher expression of various cytokines than in non-IBC patients. In vitro cell culture models of non-IBC and IBC cell lines were grown in media conditioned with and/without WF for 48 h. Afterwards, we assessed cell viability, the expression of CSCs and EMT-specific genes, and tumor invasion. Genes associated with CSCs properties and EMT markers were regulated in cells seeded in media conditioned by WF. IBC-WF exhibited a greater potential for inducing IBC cell invasion than non-IBC cells. The present study demonstrates the role of the post-surgical tumor cavity in IBC recurrence and metastasis.